Análise do conteúdo de geometria espacial em livros didáticos do ensino médio: uma atividade no âmbito da formação inicial de professores - Militz, Mari Lucia (2016)
This paper presents a survey within the framework of teacher education from a textbook analysis activity offered by the National Textbook Program. With this, the aim is to investigate how the process of assigning meaning around the content of Spatial Geometry by academics of course degree in mathematics at the Universidade Federal de Santa Maria. For this, we used the preparation of conceptual maps (Novak, 1984) as a method for the evaluation of existing concepts in cognitive structure of participants and a screenplay by analysis, which contained the steps of analysis and, finally, a questionnaire with subjective questions about the activity carried out. This work was conducted in the contributions of the theory of meaningful learning (Ausubel, 2003), which defines the meaningful learning as the relationship between the concepts present in the cognitive structure (subsumer) and which will be learned. Besides, sets a potentially significant material as being that able to relate to the prior knowledge of the learner. That way, you want to show to future teachers a educational material cannot be chosen anyway as instructional material, it is necessary to know if your student will be able to learn the desired content through the way it is exposed in the book. With the activity performed, one can show the importance of this conscious choice, since, when research participants drew up a second concept map in order to detect learning met cases where failed to learn from the material which were told to analyze.